2020
DOI: 10.1200/jco.19.01203
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplement Use During Chemotherapy and Survival Outcomes of Patients With Breast Cancer Enrolled in a Cooperative Group Clinical Trial (SWOG S0221)

Abstract: PURPOSE Despite reported widespread use of dietary supplements during cancer treatment, few empirical data with regard to their safety or efficacy exist. Because of concerns that some supplements, particularly antioxidants, could reduce the cytotoxicity of chemotherapy, we conducted a prospective study ancillary to a therapeutic trial to evaluate associations between supplement use and breast cancer outcomes. METHODS Patients with breast cancer randomly assigned to an intergroup metronomic trial of cyclophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
120
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 22 publications
0
120
0
4
Order By: Relevance
“…At present, clinical recommendations say that cancer patients, independently of age, should rather not take antioxidants during therapy [21][22][23]. In a recent study, Ambrosone et al concluded that the use of antioxidant supplements during chemotherapy, as well as iron and vitamin B12, might increase the risk of breast cancer recurrence and mortality [24]. However, this study did not stratify patients according to age, and the main age of patients enrolled in the study was about 50 years.…”
Section: Nutrition Aging and Cancer In The Elderlymentioning
confidence: 85%
“…At present, clinical recommendations say that cancer patients, independently of age, should rather not take antioxidants during therapy [21][22][23]. In a recent study, Ambrosone et al concluded that the use of antioxidant supplements during chemotherapy, as well as iron and vitamin B12, might increase the risk of breast cancer recurrence and mortality [24]. However, this study did not stratify patients according to age, and the main age of patients enrolled in the study was about 50 years.…”
Section: Nutrition Aging and Cancer In The Elderlymentioning
confidence: 85%
“…Various studies suggest that a different approach regarding vitamin use is recommended for cancer patients. A recent study by Ambrose et al (2020), highlights that the use of multivitamin and antioxidants before and during chemotherapy could have a negative impact on recurrence and overall survival in women with BC [49]. Therefore, our study adds to the overall knowledge regarding vitamin D levels in recently diagnosed treatment-naïve women with BC.…”
Section: Discussionmentioning
confidence: 63%
“…To determine whether SLC19A2 expression is predictive of responses to ASNase-containing regimens and patient survival, it would be necessary to measure patient plasma thiamine levels during treatment since having supraphysiological levels could affect response. Another possibility is to document vitamin supplementation during clinical trials, which has been done for those with antioxidant properties like vitamin E, and their use is now discouraged while undergoing chemotherapy and radiotherapy for various cancers ( 28 30 ). Collectively, our work adds to the growing list of studies available that probe whether excess vitamin supplementation may be detrimental during chemotherapy ( 31 ).…”
Section: Discussionmentioning
confidence: 99%